Comparative evaluation of preservation and growth of spruce climatypes based on long-term provenance trials in Russia - Nikolaeva, Marina A.; Faizulin, Danial Kh.; Potokin, Alexander Ph.; Jamaleev, Oleg A. (Folia Forestalia Polonica, 2014)
The article presents the results of provenance trials carried on the Norway spruce (Picea abies (L.) Karst.), the Siberian spruce (Picea obovata Ledeb.) and hybrid forms of these two species. The trails were laid in 1977–1978 according to wide-scale All-Union program of 1972 year (Prokazin 1972) in the Arkhangelsk, Vologda, Leningrad regions and the Republic of Bashkortostan. The results of the most recent inventory of provenance trials as well as analyses of preservation and growth of spruce progenies with different geographical origin are presented. One of the main factors affecting spruce progeny survival was north-south distance between seed collection locality and test locality. At the time of the study (2010–2012), in the Vologda and Arkhangelsk regions, spruce progeny preservation was higher in the case of mother stands distant to the north. On the contrary, in the Leningrad region and the Republic of Bashkortostan, preservation of northern climatypes’ progenies was lower during the whole period of plantations’ growth. With the change of seed collection locality towards west-east direction, a correlation between progeny preservation and geographical origin factors was non-existent (Vologda, Arkhangelsk regions) or weak (Leningrad region, Republic of Bashkortostan). The most successful growth and the lowest preservation were observed under the conditions of sharp-continental climate, in provenance trials carried out in the Bashkortostan Republic. In the north of Russia, in provenance trials in the Arkhangelsk region there was observed the slowest spruce growth. On the whole, at all the objects under investigation, Norway spruce progenies and hybrid forms with Norway spruce properties showed better growth parameters when compared to those of the Siberian spruce.